From Bach's Goldberg to Beethoven's Diabelli : influence and independence - Kanwischer, Alfred (Rowman and LIttlefield, 2014)
In From Bach's Goldberg to Beethoven's Diabelli: Influence and Independence, music scholar and noted pianist Alfred Kanwischer takes readers on an extended exploration in which each of the thirty-three pieces making up Beethoven's Diabelli Variations (Op. 120) is caringly examined and assessed for its ingredients, actions, personality, and influence on the whole. Counterpoint abounds, not only in the fugal variations, which are closely parsed, but throughout the Diabelli, revealing the noticeably baroque character of the technical compositional devices Beethoven employs.